WEIGHTING THE MATERIAL REQUIREMENTS OF NFRC BY USING FUZZY AHP WITH EXTENT ANALYSIS - Farhan Han, S.N.M.; Mastura, M.T.; Mansor, M.R.; Abdul Kudus, S.I.; Pradel, P. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Natural fiber reinforced composite (NFRC) are developed well recently as it is an environmentally friendly material. The increase in attention for NFRC in additive manufacturing is parallel with the awareness to replace synthetic fiber in formulation of composites. The purpose of this study is to define the suitable NFRC filament for fused deposition modelling (FDM). In this paper, Fuzzy Analytic Hierarchy Process, (Fuzzy AHP) method with extent analysis was applied in the weighting of material requirements of NFRC filament for FDM. The selection of material requirements was conducted based on physical properties, chemical properties and mechanical properties of selected natural fiber. From literature review, nine material requirements were identified as the alternatives to achieve the objectives. Fuzzy AHP is used to establish fuzzy comparison matrices for each alternatives and extent analysis is used to satisfy the goal. The result showed that Young’s modulus is the important material requirements for NFRC filament used in FDM. The selection of material requirements is important to ensure higher degree of confidence for utilization of NFRC filament for FDM.